A presença negra na universidade e a luta antirracista: análise de regulamentações internas e das provas vestibulares de língua portuguesa da USP e da UNICAMP, de 2010 a 2020 - Silva, Dayse Mara Ramos da (2024)
This work aims at investigating the effects of polices of affirmative action in Brazil after the publication of the Law nº 12.711/12, known as “Quota Law”, seeking to understand struggles and resistance associated with the presence of black people in the Paulista university courses, in the institutions Universidade de São Paulo (USP) e Universidade Estadual de Campinas (UNICAMP). To do so, two focuses of analysis: the first, about institutional journals, Jornal da USP and Jornal da UNICAMP, instruments for the publication of articles, interviews and editorials which reflect tensions and discussions carried out in the period about topics such as inequalities, racial hierarchization, social and racial-ethnic quotas; the second, Portuguese language tests from entrance university tests (vestibulares) from two universities in the period from 2010 to 2020. It is brought up, thus, the discussion about structural and institutional racism in these places via the understanding of the Society Critique Theory, the data of publications of The Brazilian Geography and Statistics Institute (IBGE), reflections of theories about sorts of racism, affirmative and racial inequality policies, to identify the kind of social unfolding in the access to university courses in these institutions. The analysis considers theme choices of question stems, authors, selection of compulsory literature works to be read, caused by laws whose intentions are antiracist practices. In order to do it, the Society Critique Theory shall be an important instrument for the comprehension of the colonization, oppression and racism. Still, the investigation affects the structural racism and the reflects on the Brazilian society, which is essential to the understating the struggles and conflicts referring to a higher turnout of black students at universities in the latest years, showing how entrance university tests and institutional journals absorbed and responded to such demands. The investigation even taps into structural racism and its reflexes in the Brazilian society, which is essential to the understanding of the conflicts referring to the higher turnout of black people at universities in the latest years, showing how university entrance tests (vestibulares) and institutional journals absorbed and responded to such demands